Representation, COVID-19, and failed metaphor: A critical analysis of the Bay of Plenty District Health Board vaccine booklet - Rangiwai, Byron (Te Kaharoa, 2021)
This paper will critically analyse the Bay of Plenty District Health Board’s (BOPDHB) controversial vaccine booklet, which featured mataora-adorned cartoon images of the COVID-19 virus. This imagery caused a furore with anecdotal evidence from social media suggesting that Māori were outraged by the portrayal of Māori in this way.This paper will offer two arguments. The first argument builds on Hokowhitu’s (2001) work, which deconstructed representations of Māori as animalistic, savage-barbarian, physical-unintelligent, mythical, bewildered-childlike, and romanticised-noble. The first argument will extend Hokowhitu’s (2001) analysis by deconstructing the representation of Māori as disease-virus. While it is impossible to understand the BOPDHB’s intentions, the second argument posits that the objective might have been to use the concept of taniwha as a metaphor for COVID-19. Though this argument is significantly weaker than the first, it still warrants some exploration, even if only to provide a sense of balance to this paper.